Efficacy and Safety of the Duodeno-Jejunal Bypass Liner in Patients With Metabolic Syndrome: A Multicenter Randomized Controlled Trial (ENDOMETAB). Issue 5 (November 2020) - Caiazzo, Robert; Branche, Julien; Raverdy, Violeta; Czernichow, Sébastien; Carette, Claire; Robert, Maud; Disse, Emmanuel; Barthet, Marc; Cariou, Bertrand; Msika, Simon; Behal, Helene; Denies, Fanette; et al.
Abstract : Objective: The aim of this study was to compare the efficacy and safety of 12-month implantation of a duodeno-jejunal bypass liner (DJBL) with conventional medical care in patients with metabolic syndrome (MS). Summary Background Data: DJBL is an endoscopic device for treating obesity and related disorders. The persistence of favorable results after 6 months has not been tested in a controlled study. Methods: We conducted a multicenter randomized controlled trial, stratified by center and diabetes status. The primary endpoint was the remission of MS at 12 months. The secondary endpoints included body mass index (BMI), glucose control, blood pressure, and lipids, assessed at 12 months after implantation, and again, at 12 months after the removal of the DJBL. Up to 174 subjects were planned to be randomized into either the DJBL or the control arm at a 2:1 ratio, respectively. Study enrollment was discontinued by the Scientific Monitoring Committee due to the early termination of the ENDO trial (NCT01728116) by the US Food and Drug Administration. The study was terminated after withdrawal of the device's European Conformity marking by the European Medicines Agency, and an interim analysis was performed. Results: A total of 82 patients were enrolled (67.5% female, 48.8% with diabetes). At 12 months after randomization, the primary endpoint was met in 6 (12%) DJBL patients and 3 (10%) controls ( P = 0.72). Patients in the DJBL group experienced greater BMI loss [mean adjusted difference (95% confidence interval, CI) −3.1 kg/m 2 (−4.4 to −1.9) kg/m 2, P < 0.001] and HbA1c change [mean adjusted difference −0.5% (95% CI −0.9 to −0.2); P < 0.001] than those in the control group. No difference remained statistically significant at 12 months after the removal of the DJBL. In the DJBL group, 39% of patients experienced at least one device-related serious adverse event, which was classified as Grade III Dindo-Clavien in 22%, and required premature device explantation in 16%. Conclusions: The present study showed a transient clinical benefit of DJBL, which was only apparent at 1 year, when the device was still in situ, and was obtained at the risk of serious device-related adverse events in 39% of patients. These results do not support the routine use of DJBL for weight loss and glucose control in patients with MS. Abstract : Supplemental Digital Content is available in the text